2022
DOI: 10.1109/access.2022.3171226
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Today’s Malware and Its Distribution Network: Common Adversary Strategies and Implications

Abstract: Malware has plagued the internet and computing systems for decades. The war against malware has always been an arms race. Researchers and industry have constantly improved detection and prevention methodologies against increasingly more evasive malware. Keeping up with the constantly changing adversary tactics for evading defensive efforts and maintaining an efficient malware supply chain is imperative to stay ahead in the competition. In this paper, we present a large-scale and comprehensive analysis of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…MDNs comprise networks of various sizes. These networks consist of landing sites, redirects, exploit kits (EKs), and malware [1][2][3][4]. Here, the exploit kits, such as RIG and Redkit, exploit the users' PCs.…”
Section: Introductionmentioning
confidence: 99%
“…MDNs comprise networks of various sizes. These networks consist of landing sites, redirects, exploit kits (EKs), and malware [1][2][3][4]. Here, the exploit kits, such as RIG and Redkit, exploit the users' PCs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these limitations, machine learning-based techniques have been used to identify the bots that behave like normal connections and generate legitimate traffics. Many studies have surveyed the available botnet detection techniques and found that machine learning-based techniques can detect real-world botnets regardless of botnet protocol and structure with a very low false-positive rate [8], [30], [28], [29].…”
Section: Introductionmentioning
confidence: 99%
“…Due to these limitations, machine learning-based techniques have been used to identify the bots that behave like normal connections and generate legitimate traffics. Many studies have surveyed the available botnet detection techniques and found that machine learning-based techniques can detect real-world botnets regardless of botnet protocol and structure with a very low false-positive rate [8], [30], [28], [29].…”
Section: Introductionmentioning
confidence: 99%